Business Revenue Enhancement Through Micro Credit: Case Study on MSME at Cimahi Keripik Pojok Center - Nurhayati, Nurhayati; Maulana, Muhammad Fikri; Anggraeni, Nurul Meilani; Destianti, Selvia Nur (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
This research aims to identify the implementation and effectiveness of Micro Credit distribution in enhancing business earnings for micro-enterprises in Cimahi, focusing on the Cimahi Keripik Pojok Center. It also investigates the constraining factors faced by these micro-entrepreneurs in accessing and utilizing Micro Credit. The study employs a qualitative descriptive research design, utilizing case study methods to gather detailed information from 15 micro-entrepreneurs at the Cimahi Keripik Pojok Center. Data was collected through observations, interviews, and questionnaires, and analyzed using data reduction, data presentation, and conclusion drawing techniques. Triangulation was used to ensure data validity. The research found that Micro Credit significantly enhances business revenue for micro-entrepreneurs. However, several constraints were identified, including lack of socialization about Micro Credit, complicated bureaucratic processes, high-interest rates, and inadequate collateral. Despite these challenges, entrepreneurs who accessed Micro Credit reported increased capital and production capabilities, which led to higher income and improved business stability. The study's findings highlight the need for improved socialization and simplified processes for accessing Micro Credit. Policymakers and financial institutions should focus on making Micro Credit more accessible and affordable, ensuring that micro-entrepreneurs can leverage these loans for business growth. This research contributes to the understanding of how Micro Credit can be optimized to support MSMEs, ultimately fostering economic development and reducing poverty